Solid Lipid Nanoparticles: A Strategy to Improve Oral Delivery of the Biopharmaceutics classification system (BCS) Class II Drugs: Solid Lipid Nanoparticles: A Strategy to Improve Oral Delivery of the Biopharmaceutics classification system (BCS) Class II Drugs - Kumar, Hitesh (International Journal of Pharmaceutical & Biological Archive, 2019)
In drug discovery, approximately 70% of new drug candidates have shown poor aqueous solubility in recent years. Currently, approximately 40% of the marketed immediate release (IR) oral drugs are categorized as practically insoluble (<100 g/mL). The aqueous solubility of a drug is a critical determinant of its dissolution rate. The Biopharmaceutics Classification System (BCS) is a useful tool for decisionmaking in formulation development from a biopharmaceutical point of view. BCS Class II drugs are identified as low solubility and high permeability. In general, the bioavailability of a BCS Class II drug is rate limited by its dissolution so that even a small increase in dissolution rate sometimes results in a large increase in bioavailability. Therefore, an enhancement of the dissolution rate of the drug is thought to be a key factor for improving the bioavailability of BCS Class II drugs. Solid lipid nanoparticles (SLNs) were developed in the mid-1980s as an alternative system to the existing traditional carriers (emulsions, liposomes, microparticles, and their polymeric counterparts) when Speiser prepared the first micro- and nano-particles (named nano pellets) made up of solid lipids for oral administration. SLNs are colloidal carriers made up of lipids that remain solid at room temperature and body temperature and also offer unique properties such as small size (50–500 nm), large surface area, high drug loading, and the interaction of phases at the interfaces and are attractive for their potential to improve performance of pharmaceuticals, nutraceuticals, and other materials. Moreover, SLN are less toxic than other nanoparticulate systems due to their biodegradable and biocompatible nature. SLN is capable of encapsulating hydrophobic and hydrophilic drugs, and they also provide protection against chemical, photochemical, or oxidative degradation of drugs, as well as the possibility of a sustained release of the incorporated drugs.